Surgical Treatment of Left Atrial Dissection and Severe Mitral Valve Obstruction. Issue 2 (12th June 2021) - Chen, Antian; Ma, Guotao; Yang, Deyan; Wang, Chenyu; Liu, Yingxian
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Left atrial dissection is a rare complication of mitral valve replacement surgery. Here, a case of left atrial dissection followed by mitral valvular obstruction was presented. It is suspected that the dissection was caused by trematodiases infection. Cardiac surgery was finally performed, which not only confirmed the diagnosis but also acted as an effective treatment. Especially, surgery is of essential value to confirm the perforation locating at the basal posterior wall of the left ventricle, to repair the atrial dissection, and to relieve the mitral valvular obstruction.